Greatest hits [compact disc] - Lambert, Miranda, 1983-; Ballerini, Kelsea, 1993- (Capitol Nashville, 2024)
Multi-platinum, Grammy Award-winning four-piece Little Big Town releases their first-ever career-spanning greatest hits album via Capitol Records Nashville. The album collects over two decades of chart-busting country smashes on one definitive body of work, ranging from the Grammy Award-winning Pontoon; Boondocks; and Better Man to massively influential anthems such as Girl Crush. It traces the quartet's unbelievable journey from humble beginnings to country royalty.